PENYAKIT HAWAR DAUN PINUS MERKUSII DI BERBAGAI PERSEMAIAN KAWASAN UTAMA HUTAN PINUS JAWA TIMUR - Sutarman .; Andriani Eko Prihatiningrum (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2015)
Leaf blight disease of Pinus merkusii in various nurseries of pine forest in major area of East Java. This study aims to: (i) obtain isolates of pathogens, (ii) determine disease on seedling growth during the critical period and the young plants, (iii) determine the effect of pathogenic isolates on disease severity, and (iv) determine the effect of altitude on severity of seedling’s leaf blight disease of Pinus merkusii from various nursery locations in East Java. The experiment was conducted in February-August 2014 at nine locations in the nursery and one young pine plantation site. Disease index data were analyzed using Microsoft Office Excel 2007 software to determine the regression model of the relationship between the index of disease with the independent variables and with Anova followed by Duncan test to find out the effect of altitude difference to the index of disease. Pathogen that causes late blight is Pestalotia theae Sawada. In the critical period, seedling disease index increased from 7.38 to an average of 26.96 in the nursery RPH Celaket; while on the young plants in the field in RPH Kemiri disease index ranged 28-31. Differences in altitude did not affect disease index difference. Based on disease index, three isolates of pathogens that require serious attention are Wagir isolates (985 m asl., the most virulent), Ngantang (500 m asl.), and South Pujon (1200 m asl.).